2019
DOI: 10.1002/mc.22989
|View full text |Cite
|
Sign up to set email alerts
|

Sohlh2 inhibits breast cancer cell proliferation by suppressing Wnt/β‐catenin signaling pathway

Abstract: Sohlh2 belongs to the superfamily of basic helix‐loop‐helix (bhlh) transcription factors. Aberrant expression of bhlh transcription factors has been shown to be associated with multiple tumorigenesis. We previously identified that sohlh2 functioned as a tumor suppressor in ovarian cancer. Here, we examined the expression levels of sohlh2 in human breast cancer and its potential role in disease pathogenesis. The results of sohlh2 immunohistochemistry (IHC) and Western blot analysis demonstrated the decreased so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 35 publications
0
12
0
Order By: Relevance
“…Then, 2 independent diagnosticians calculated the semi-quantitative immunoreactivity score (IRS), according to a staining intensity scale: No staining, 0; weak staining, 1; moderate staining, 2; and strong staining, 3; and the number of stained cells: 0, 0; 1-25, 1; 26-50, 2; 51-75, 3; and 76-100%, 4. The final IRS ranged from 0 to 12, and was determined by multiplying the intensity scores with the percent of positively stained cells, as described previously (25).…”
Section: Immunohistochemistry (Ihc)mentioning
confidence: 99%
“…Then, 2 independent diagnosticians calculated the semi-quantitative immunoreactivity score (IRS), according to a staining intensity scale: No staining, 0; weak staining, 1; moderate staining, 2; and strong staining, 3; and the number of stained cells: 0, 0; 1-25, 1; 26-50, 2; 51-75, 3; and 76-100%, 4. The final IRS ranged from 0 to 12, and was determined by multiplying the intensity scores with the percent of positively stained cells, as described previously (25).…”
Section: Immunohistochemistry (Ihc)mentioning
confidence: 99%
“…Li et al showed that TRIM63, a novel oncogene, promotes BC cell proliferation and migration via activating the Wnt/ β -catenin signaling pathway [ 34 ]. Also, the silencing of SOHLH2 enhances BC cell proliferation by activating the Wnt/ β -catenin signaling pathway [ 35 ]. Given that SOX4 could stimulate β -catenin activity [ 36 38 ], we surmised that circ-DONSON could activate the Wnt/ β -catenin signaling via SOX4.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hands, SOHLH2 silence increased migration and invasion, suggesting that this protein may negatively regulate metastasis and play an important role in EMT (Ji et al, 2016). Primary breast tumors express reduced levels of SOHLH2 in comparison with normal tissue (Zhang et al, 2019). Also, SOHLH2 expression is associated to cellular proliferation in vitro and tumor growth in vivo acting as a tumor suppressor gene.…”
Section: Breast Cancermentioning
confidence: 99%
“…Also, SOHLH2 expression is associated to cellular proliferation in vitro and tumor growth in vivo acting as a tumor suppressor gene. The tumor suppressor effects on breast cancer seem to occur due to SOHLH2 inhibition of WNT/β-catenin through the increase of APC (Zhang et al, 2019) (figure 2). Previous data from our group have shown the association between SOHLH2 and triple negative breast cancer (TNBC).…”
Section: Breast Cancermentioning
confidence: 99%